2014
DOI: 10.1111/anu.12130
|View full text |Cite
|
Sign up to set email alerts
|

Adult triploid Atlantic salmon (Salmo salar) have higher dietary histidine requirements to prevent cataract development in seawater

Abstract: The study investigated cataract preventive effects of dietary histidine (His) supplementation in triploid Atlantic salmon during seawater grow-out. Groups of individually PIT tagged diploid (2N) and triploid (3N) postsmolts were fed one of two supplemented dietary histidine levels; low (L, 12.6 g kg-1 diet) or high (H, 17.4 g kg-1 diet) from March to September following their first sea winter. Low severity cataracts were detected in both ploidy prior to supplemented His diet application. Thereafter, 3N-L showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 42 publications
0
43
1
Order By: Relevance
“…For example, triploid salmon may require more dietary phosphorus than diploids (Burke et al 2010), and require dietary supplements of histidine to reduce the incidence of ocular cataracts (Taylor et al 2014). In addition, diploid and triploid Atlantic salmon may differ in gut microbiota, with potential consequences for culture performance and health (Cantas et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, triploid salmon may require more dietary phosphorus than diploids (Burke et al 2010), and require dietary supplements of histidine to reduce the incidence of ocular cataracts (Taylor et al 2014). In addition, diploid and triploid Atlantic salmon may differ in gut microbiota, with potential consequences for culture performance and health (Cantas et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although the reasons for this are not clear, differences in egg quality (Taylor et al 2011) and nutritional requirements (Burke et al 2010;Taylor et al 2014) might be key factors.…”
Section: Introductionmentioning
confidence: 99%
“…; Taylor et al . , ). The underlying causes for these abnormalities are currently unknown, but they likely arise from one or more genotypic, environmental or nutritional effects that are exacerbated by triploidy due to altered gene dosage/expression or increased cell size.…”
Section: Impacts Of Triploidy On Phenotypic Characteristics Relevant mentioning
confidence: 99%
“…In an experiment specifically designed to determine the cause of higher cataract incidence in triploid Atlantic salmon, Taylor et al . () formulated two test diets that varied in histidine content, knowing that dietary supplementation of this amino acid reduces the incidence and severity of cataracts in diploid Atlantic salmon. This study clearly showed triploids to have a higher dietary histidine requirement than diploids for reducing the severity of cataracts once they have developed in postsmolts.…”
Section: Impacts Of Triploidy On Phenotypic Characteristics Relevant mentioning
confidence: 99%
“…However, recent developments in production techniques have solved some of the early challenges experienced with commercial production of triploids (Fjelldal and Hansen 2010;Fraser et al 2012;Frenzl et al 2014;Leclercq et al 2011;Taylor et al 2015). In Norway, which is the worlds largest Atlantic salmon producing country, recent government licensing schemes have encouraged companies to initiate triploid production at a commercial level.…”
Section: Discussionmentioning
confidence: 99%